2021
DOI: 10.2355/isijinternational.isijint-2020-610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micro-texture Distribution and Straining Direction on the Ridging of Ferritic Stainless Steels

Abstract: Ridging means the appearance of surface profile undulations, i.e. peaks and valleys, as a result of plastic strain. The reasons for the different ridging behaviour of industrially produced, stabilized ferritic stainless steel sheets (EN 1.4509) have been investigated after straining in the rolling and transverse directions with low and high resistance towards ridging. The evolution of macro-texture has been measured by X-ray diffraction (XRD) both before and after ridging tests in the rolling and transverse di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Several studies have investigated the texture evolution of FSSs during forming processes using different techniques such as X-ray diffraction (XRD) [8][9][10][11][12], electron backscatter diffraction (EBSD), and scanning electron microscopy (SEM), [8][9][10][11][12][13][14][15][16][17][18] and only a small number of studies employed transmission electron microscopy (TEM) [13,19]. Some of these studies focused on cold-worked FSSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the texture evolution of FSSs during forming processes using different techniques such as X-ray diffraction (XRD) [8][9][10][11][12], electron backscatter diffraction (EBSD), and scanning electron microscopy (SEM), [8][9][10][11][12][13][14][15][16][17][18] and only a small number of studies employed transmission electron microscopy (TEM) [13,19]. Some of these studies focused on cold-worked FSSs.…”
Section: Introductionmentioning
confidence: 99%
“…Others studied the texture evolution to understand the ridging process that FSSs may experience during forming, like Ma et al [16], who found that this defect is avoided by preventing the formation of coarse bands and grains with the {001} component in 430 and 430 LR. However, most of these studies focused on the most popular standard grade of FSSs, AISI 430 [11,16], while others explored the texture evolution of modified grades with higher contents of Ti and Nb, which have improved corrosion resistance and weldability [8][9][10][13][14][15][17][18][19]. None of these works studied the influence of the slight modification of the typical alloy elements of AISI 430 standard composition, such as Si, Mn, Cr, C, and N. Moreover, there is a lack of comprehensive and comparative analysis of the texture evolution of different grades of FSSs after deep drawing and its relation to their formability and mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that coarse banded structure of colonies [5], known as grain colonies, is responsible for ridging. Different grain colonies and matrix are likely to show different plastic anisotropies [4][5][6], leading to ridging. In almost every process of FSS manufacturing, such as casting [5,7,8], hot rolling [9,10] and cold rolling [4,8], the correlation between grain colonies and ridging has been observed.…”
Section: Introductionmentioning
confidence: 99%